Vitamin C and E Treatment Blocks Changes in Kynurenine Metabolism Triggered by Three Weeks of Sprint Interval Training in Recreationally Active Elderly Humans - Victoria L. Wyckelsma; Ada Trepci; Lilly Schwieler; Tomas Venckunas; Marius Brazaitis; Sigitas Kamandulis; Henrikas Paulauskas; Helena Gapeyeva; Mati Pääsuke; Stefano Gastaldello; Sophie Imbeault; Håkan Westerblad; et al. (MDPI AG, 2021)
The kynurenine pathway (KP) is gaining attention in several clinical fields. Recent studies show that physical exercise offers a therapeutic way to improve ratios of neurotoxic to neuroprotective KP metabolites. Antioxidant supplementation can blunt beneficial responses to physical exercise. We here studied the effects of endurance training in the form of sprint interval training (SIT; three sessions of 4-6 × 30 s cycling sprints per week for three weeks) in elderly (~65 years) men exposed to either placebo (n = 9) or the antioxidants vitamin C (1 g/day) and E (235 mg/day) (n = 11). Blood samples and muscle biopsies were taken under resting conditions in association with the first (untrained state) and last (trained state) SIT sessions. In the placebo group, the blood plasma level of the neurotoxic quinolinic acid was lower (~30%) and the neuroprotective kynurenic acid to quinolinic acid ratio was higher (~50%) in the trained than in the untrained state. Moreover, muscle biopsies showed a training-induced increase in kynurenine aminotransferase (KAT) III in the placebo group. All these training effects were absent in the vitamin-treated group. In conclusion, KP metabolism was shifted towards neuroprotection after three weeks of SIT in elderly men and this shift was blocked by antioxidant treatment.